2008
DOI: 10.1371/journal.pone.0002702
|View full text |Cite
|
Sign up to set email alerts
|

Native Bacterial Endophytes Promote Host Growth in a Species-Specific Manner; Phytohormone Manipulations Do Not Result in Common Growth Responses

Abstract: BackgroundAll plants in nature harbor a diverse community of endophytic bacteria which can positively affect host plant growth. Changes in plant growth frequently reflect alterations in phytohormone homoeostasis by plant-growth-promoting (PGP) rhizobacteria which can decrease ethylene (ET) levels enzymatically by 1-aminocyclopropane-1-carboxylate (ACC) deaminase or produce indole acetic acid (IAA). Whether these common PGP mechanisms work similarly for different plant species has not been rigorously tested.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(138 citation statements)
references
References 39 publications
5
124
0
3
Order By: Relevance
“…The bacterium thus can act as a sink for ACC and lower ethylene level in plants, preventing the potentially deleterious consequences of high ethylene concentrations (Glick, P enros e, & Li, 1998). Production of ACC deaminase and IAA is an important and efficient way for plant growth promoting microorganisms to manipulate their plant hosts (Long, Schmidt, & Baldwin, 2008). IAA is a phytohormone involved in root initiation, cell division and cell enlargement (Salisbury, 1994) that enhances root growth and root length, resulting in greater root surface area and enables the plant to access more nutrients from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium thus can act as a sink for ACC and lower ethylene level in plants, preventing the potentially deleterious consequences of high ethylene concentrations (Glick, P enros e, & Li, 1998). Production of ACC deaminase and IAA is an important and efficient way for plant growth promoting microorganisms to manipulate their plant hosts (Long, Schmidt, & Baldwin, 2008). IAA is a phytohormone involved in root initiation, cell division and cell enlargement (Salisbury, 1994) that enhances root growth and root length, resulting in greater root surface area and enables the plant to access more nutrients from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Among them are comprised bacterial diazotrophs that do not form nodules on hosts, such as Azospirillum species, and some Rhizobium species. Isolated from a large diversity of plants (Rosenblueth & Martínez-Romero, 2006), in general they occur at lower population density than rizospheric bacteria or bacterial pathogens and can positively affect host plant growth (Long et al, 2008). What makes bacterial endophytes suitable as biocontrol agents is their colonization of an ecological niche similar to that of phytopathogens (Ryan et al, 2008).…”
Section: Plant-microorganism Interactions: Ecological Implicationsmentioning
confidence: 99%
“…thivervalensis sp. are typically plant-associated bacteria, they have been isolated as endophyte from Solanum nigrum (Long et al 2008) and from Arabidopsis thaliana and Brassica napus roots (Achouak et al 2000). This work shows that they produce the high affinity siderophore pyoverdine (PYO thi ) and the lipopeptidic siderophore histicorrugatin under iron limiting conditions to fulfill their need for iron.…”
Section: Discussionmentioning
confidence: 99%
“…1). Screening of an in house IEF data set of pyoverdine samples of a large collection of more than 450 strains revealed an additional strain, the endophyte P. brassicacearum BGCR2-9(1) from Solanum nigrum (Long et al 2008), with the same IEF profile. LC-MS analysis confirmed that this strain also produces PYO thi .…”
Section: --mentioning
confidence: 99%